Gambaran Tingkat Stress Pada Pasien Covid-19 Di Ruang Isolasi - Wijaya, Siswanto Agung; Agustin, Ratna; Rahayu, Dian Putri (Indonesian Academia Health Sciences Journal, 2021)
Objective: to identify the level of stress experienced by covid-19 patients in the Al-Aqsa isolation room . Methods: This article This study used a descriptive method that was carried out on patients who were confirmed positive COVID-19 in the Al-Aqsa isolation room on the 6th floor of the Haji General Hospital Surabaya with the Accidental Sampling . The samples obtained were 30 respondents. The research instrument used in this research aiming at describing the stress experienced by respondents was DASS 42 questionnaire Results: The results showed that 23.3% of respondents experienced normal stress conditions, 53.3% experienced mild stress, 20.0% of respondents experienced moderate stress, and 3.3% of respondents experienced severe stress Conclusion: 7 (23.3%) respondents experienced moderate stress, 16 (53.3%) respondents experienced mild stress, 6 (20.0%) respondents experienced moderate stress, and 1 (3.3%) respondent experienced severe stress. Which is suspected to be influenced by age and gender factors